Brine reject dilution with treated wastewater for indirect desalination. (1st November 2021) - Khanafer, Daoud; Ibrahim, Idris; Yadav, Sudesh; Altaee, Ali; Hawari, Alaa; Zhou, John
Abstract: The forward osmosis (FO) process was suggested as a pretreatment to a multi-stage flashing (MSF) plant to reduce the environmental impact of brine discharge and the chemicals used. Yet, there is no study investigating the performance of the FO process pretreatment to the MSF plant using tertiary sewage effluent (TSE) as a feed solution. Combining MSF brine with the TSE generates a considerable permeation flux, reducing the membrane area and capital cost. This study evaluated the performance of the FO process for indirect desalination of the MSF brine, considering membrane fouling, cleaning, required membrane area and the specific power consumption. The FO process used a thin-film composite (TFC) membrane to dilute the brine reject from the MSF plant by the TSE and hence converting waste solutions into a feasible water resource. A considerable high water flux (±35 L/m 2 h) was generated and slightly decreased throughout each experiment's 4 cycles. An enhancement in the water permeability was observed in the FO tests with a prefiltration of the brine reject and the wastewater with 20 μm and an osmotic backwash cleaning of the used membrane. The prefiltration of the draw and feed solutions was effective in minimizing the impact of fouling. Maximum power consumption of 0.007 kWh/m³ was consumed in the forward osmosis process without prefiltration and decreased to 0.006 kWh/m³ in the FO process. The proposed FO system successfully diluted the brine reject' divalent ions, reducing their concentration to 43% in some cases. Depending on the FO membrane orientation, the TSE feed solution resulted in a 276%–473% reduction in the number of FO elements required in the FO process compared to the seawater feed solution. Graphical abstract: Image 1 Highlights: 35 L/m 2 h water flux was achieved in the FO process for diluting MSF brine. Membrane cleaning was performed with osmotic backwash at 40 °C. Water flux decline was 6% in the 4th filtration cycle of the FO process. Specific power consumption for FO and prefiltration processes is 0.006 kWh/m 3 .